A note on an investigation of the surface grinding process with examples of wheel and coolant selection and planning data - Purcell, J. (College of Aeronautics, 1956)
This note deals with an investigation into the establishment of manufacturing techniques, on a production scale, for surface grinding, high tensile heat resistant alloy sheet approximately 7 feet by 5 feet. Rigid manufacturing tolerances are demanded in which surface finish must not exceed 10 micro-inches and the thickness tolerance is plus or minus 0. 0002 inches. The information contained in this report applies to the surface grinding process in general and can be used to aid production planning, as a correct estimate of wheel life when operating under set conditions can be made, and the necessary time for redressing allowed. Results from the work carried out suggest that it may be beneficial to pass components to be surface ground under a roughing wheel (Lumsden) type machine, which will set the constant metal thickness for final finishing. In this way a correct estimated time could be allowed for the operations roughing and finish grinding at optimum conditions.